Trends in Opioid Use in a Cohort of Patients with Rheumatoid Arthritis - Manuel E. Machado-Duque; Diana Marcela Ramírez-Valencia; María Mónica Murillo-Muñoz; Jorge E. Machado-Alba (Pain Research and Management)
The objective was to determine the trend in the use of opioid analgesics in a cohort of patients diagnosed with and treated for rheumatoid arthritis (RA) in 24 cities in Colombia. This retrospective cohort study included adult patients diagnosed with RA, which was managed in a specialized institution in Colombia between January 2011 and December 2012. The first rheumatology visit was recorded as an index date, and monthly monitoring of the analgesic medication received was performed until December 2017. Sociodemographic variables, the use of opioids, and concomitant prescriptions were evaluated. A total of 1,329 patients diagnosed with and treated for RA were included; they had a mean age of 61.2 ± 11.8 years and were predominantly females (n = 936; 82.9%). A total of 1,129 (84.9%) subjects used opioids for at least one month, and a growing trend, from 13.5% to 21.4%, was observed in patients who received opioids every month throughout a 7-year follow-up of the cohort. In total, 46.7% of the cases used opioids for more than 12 months. The most commonly used opioids were codeine (76.3%) and tramadol (71.1%). All patients received conventional disease-modifying antirheumatic drugs (DMARDs), 85.6% received systemic corticosteroids, 73.9% received nonsteroidal anti-inflammatory drugs, and 15.9% received biological DMARDs. A high proportion of opioid use was shown for pain management in patients with RA, in many cases for more than 12 months, in whom the efficacy and especially safety, related to the risk of dependence, should be monitored.